Risk-synchronisation through the prism of interconnectedness among sustainability equities returns: a regional and global perspective. (19th December 2022) - Asafo-Adjei, Emmanuel; Adam, Anokye M.; Hamidu, Zulaiha; Oppong, Priscilla B.; Amoako, Gilbert K.
The study scrutinises the dynamic interconnectedness among 20 sustainability equities returns from regional and global perspective with a sample period from 12th November 2012 to 2nd December 2021. The sustainability equities returns include samples from Africa, America, Asia, Europe, BRICT, Emerging markets, Developed markets and World indices. Using the TVP-VAR and wavelet multiple techniques, we find heterogeneous levels of markets integrations. A mixture of net transmitting and net receiving assets at the averaged total connectedness and net connectedness levels are noticeable. Also, dynamic connectedness rises in times of uncertainties revealing contagion effects. Moreover, the integration levels among sustainability equities are high across investment horizons, but with a potential lead or lag. Particularly, we find more flights to quality for net receivers of shocks relative to net transmitters. It must be noted that distinctions between net transmitters and net receivers of sustainability equities should manifest across time for effective investment decisions.